2020
DOI: 10.1186/s12864-020-6655-4
|View full text |Cite|
|
Sign up to set email alerts
|

ITR-Seq, a next-generation sequencing assay, identifies genome-wide DNA editing sites in vivo following adeno-associated viral vector-mediated genome editing

Abstract: Background: Identifying nuclease-induced double-stranded breaks in DNA on a genome-wide scale is critical for assessing the safety and efficacy of genome editing therapies. We previously demonstrated that after administering adeno-associated viral (AAV) vector-mediated genome-editing strategies in vivo, vector sequences integrated into the host organism's genomic DNA at double-stranded breaks. Thus, identifying the genomic location of inserted AAV sequences would enable us to identify DSB events, mainly derive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
42
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 43 publications
2
42
0
Order By: Relevance
“…First, targeted integration can lower serum albumin levels (Zhang et al, 2019 ; Ou et al, 2020 ) and albumin mutations have been observed in human hepatocellular carcinoma (Cancer Genome Atlas Research Network, 2017 ; Rao et al, 2017 ). Second, long-term AAV-mediated expression of endonucleases can result in off-target editing and unwanted AAV insertions (Li et al, 2019 ; Breton et al, 2020 ; Wang et al, 2020c ). Finally, pre-existing liver conditions and immune responses against AAV vectors used to deliver transgenes or nucleases severely limit the number of eligible patients (Boutin et al, 2010 ; Simhadri et al, 2018 ).…”
Section: Endogenous Promotersmentioning
confidence: 99%
“…First, targeted integration can lower serum albumin levels (Zhang et al, 2019 ; Ou et al, 2020 ) and albumin mutations have been observed in human hepatocellular carcinoma (Cancer Genome Atlas Research Network, 2017 ; Rao et al, 2017 ). Second, long-term AAV-mediated expression of endonucleases can result in off-target editing and unwanted AAV insertions (Li et al, 2019 ; Breton et al, 2020 ; Wang et al, 2020c ). Finally, pre-existing liver conditions and immune responses against AAV vectors used to deliver transgenes or nucleases severely limit the number of eligible patients (Boutin et al, 2010 ; Simhadri et al, 2018 ).…”
Section: Endogenous Promotersmentioning
confidence: 99%
“…Deep sequencing could be a powerful method for validated measurement of AAV integration frequencies. 42,43 We found different parts of the AAV vector sequences inserted into DSBs in our previous work. 6 Due to the limitation of amplicon sequencing method in this study, we could not determine the extent of vector sequence integration around target region.…”
Section: Discussionmentioning
confidence: 87%
“…An HTS‐based assay was recently developed to identify off‐target nuclease activity after the AAV‐mediated genome edition in vivo. [ 32 ] In that protocol, named ITR‐Seq, PCR, and adapter optimizations are performed to specifically amplify ITR‐genomic DNA junctions. Combining multiple sequencing technologies could provide complementary information and reduce the risks associated with the inherent technical errors of each platform.…”
Section: Discussionmentioning
confidence: 99%